Digital Signal Processing System-Level Design Using LabVIEW. - Kehtarnavaz, Nasser; Kim, Namjin (Newnes [Imprint] Elsevier Science & Technology Books., 2005)
LabVIEW (Laboratory Virtual Instrumentation Engineering Workbench) developed by National Instruments is a graphical programming environment. Its ease of use allows engineers and students to streamline the creation of code visually, leaving time traditionally spent on debugging for true comprehension of DSP. This book is perfect for practicing engineers, as well as hardware and software technical managers who are familiar with DSP and are involved in system-level design. With this text, authors Kehtarnavaz and Kim have also provided a valuable resource for students in conventional engineering c.